La nature de la durabilité sociale : vers une lecture socioculturelle du développement territorial durable - Constanza Parra; Frank Moulaert (Développement Durable et Territoires)
In contemporary debates on sustainable development, social sustainability has become an important theme. But its conceptualization is often done in isolation from the other pillars of sustainable development. As a consequence it cannot fully play its role either in the analysis, or in the process of sustainable development. The authors explain how the ‘culturalisation’ of sustainable development, and in particular of social sustainability, would allow for a coherent analysis of the social dynamics of socio-ecological systems in general and their governance in particular. However, to allow culture to play its role properly, it should be better integrated into the analysis of sustainable development.